Crude glycerine in growing and finishing pigs feeding - Paulo Levi de Oliveira Carvalho (Semina: Ciências Agrárias, 2013)
Two experiments were carried out aiming to determine the nutritional value and to evaluate performance, carcass traits and economic feasibility of growing-finishing pigs fed on two types of crude glycerine (CG) which were made from vegetable oil (CGS), and mixed of animal fat + soybean oil (CGA). In Experiment I, a digestibility assay were carried out using 32 (24 test diet and 8 basal diet) cross breed pig (45.08 ± 4.11 kg). The experimental unit consisted of one pig, with a total of four experimental units per diet. Glycerine levels used in the digestibility assay were 6, 12, and 18% of the basal diet (corn + soybean meal based). The values (as-fed-basis) of DE and ME (kcal/kg) obtained were: CGS= 5,040 and 4,481; CGA= 5,234 and 4,707, respectively. In the Experiment II, 63 pigs, were allotted in a completely randomized design in 2 x 4 factorial scheme, with two types of crude glycerine (CGS and CGA) and four inclusion levels (3, 6, 9, and 12%). Additionally, it was formulated a control diet containg no glycerine (0%). There was no interaction (P≥0.05) among levels of CG and types of glycerine sources, and the regression analysis indicates no effects (P≥0.05) of crude glycerine inclusion on performance and carcass traits (backfat thickness and loin depth). The results suggest that it is feasible to use up to 12% of both crude glycerine (made from soybean oil and mixed) on growing-finishing pigs diet, without impairing performance and carcass traits, besides providing a reduction of about 11% on feeding cost.